Using Clarke Vector Approach for Stator Current and Voltage Analysis on Induction Motors with Broken Rotor Bars - Vaimann, T.; Kallaste, A.; Kilk, A. (Elektronika ir Elektrotechnika, 2012)
This paper presents the possibilities of using Clarke vector approach for stator current and voltage analysis for induction motors with broken rotor bars. The equations for performing Clarke transformation on three-phase stator current and voltage are presented. Since this method is generally used for transforming current signals, benefits for using it on voltage signals is presented. Described method can be used for effective detection of broken rotor bars in three-phase squirrel-cage induction motors. Necessity for further study is proposed. Ill. 10, bibl. 7, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2368